LEGAL ANALYSIS OF LEGAL CERTAINTY REGARDING THE USE OF AU-TOMATIC GATES (AUTOGATE) AT THE IMMIGRATION CHECKPOINT OF THE INTERNATIONAL PORT OF CITRA TRITUNAS (A RESEARCH STUDY AT THE CLASS I SPECIAL IMMIGRATION OFFICE OF TPI BATAM) - Immanuel Simanjuntak; Ramlan; Bachtiar Simatupang; Erniyanti (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
The modernization of Indonesia's immigration system through the use of digital technology is a response to the need for efficient, fast, and legally guaranteed public services. One such innovation is the use of automatic gates (autogates) at Immigration Checkpoints (TPI), including at Citra Tritunas International Port, Batam. However, the implementation of autogates as an immigration inspection tool raises various legal issues, ranging from regulatory loopholes, technical obstacles, to cultural resistance that can threaten legal certainty and the protection of user rights. This study aims to analyze the regulation and implementation of autogate use from a legal certainty perspective, as well as identify obstacles and formulate relevant solutions. This study uses normative and empirical legal methodologies, with a regulatory approach, field interviews, and direct observation at the Class I Special Immigration Office for the Batam Port Area. John Rawls' theory of justice serves as a grand theory, Lawrence M. Friedman's theory of legal systems as a middle theory, and Sudikno Mertokusumo's theory of legal certainty as an applied theory. The research findings indicate that, from a normative perspective, the use of automatic gates has been regulated through the Regulation of the Minister of Law and Human Rights No. 9 of 2024; However, this is not yet supported by detailed technical regulations, such as standard operating procedures (SOPs) and operational guidelines. Field implementation demonstrates procedural efficiency; however, it still faces technical glitches, infrastructure limitations, and low user understanding. These obstacles result in legal uncertainty and inadequate protection of user rights. Therefore, technical regulatory updates, human resource training, public awareness campaigns, and strengthened cross-sector coordination and digital-based monitoring systems are needed.